Self-regulated listening of students at transition from high school to an English medium instruction (EMI) transnational university in China. (December 2021) - Zhou, Sihan; Rose, Heath
Abstract: Listening to academic content in English medium instruction (EMI) can be particularly challenging when students transit from an L1-instructed secondary school to an EMI university. Under such circumstances, students need to quickly develop and apply new strategies to regulate their listening to lengthy and spontaneous teacher talk in their L2. This study explores the self-regulated listening of first-year Chinese students after entry to an EMI transnational university in mainland China. Data were collected from 412 students via a battery of measures of listening strategies, listening proficiency and self-efficacy to explore the role of these variables in strategic listening. Interviews were also conducted with 35 students to better understand the strategies they applied in the forethought, performance and self-reflection phases of self-regulation. Results revealed that students engaged in a holistic self-regulatory cycle of learning to cope with the transition to listening to EMI classes, where their listening experience and use of strategies in class were closely associated with their learning before and after class. Results highlighted the importance of preview activities in facilitating listening. They also emphasised the role of self-efficacy and baseline proficiency in EMI listening, which has important implications for language teaching in preparatory programs during this transition period.